Supercritical carbon dioxide extraction of seed oil from yellow horn ( Xanthoceras sorbifolia Bunge.) and its anti-oxidant activity - Zhang, Su; Zu, Yuan-Gang; Fu, Yu-Jie; Luo, Meng; Liu, Wei; Li, Ji; Efferth, Thomas (Bioresource technology, 2010)
Supercritical fluid carbon dioxide (SF-CO 2) extraction (SFE) of seed oil from yellow horn and its anti-oxidant activity were investigated. The effects of CO 2 flow rate and particle size were firstly optimized, and a central composite design (CCD) combined with response surface methodology was used to study the effects of extraction pressure, temperature and time on the extraction yields. A maximal extraction yield of 61.28% was achieved under optimal conditions of extraction pressure 30 MPa at 45.68 °C, 2.08 h and CO 2 flow rate 12 kg/h with 0.5 mm particle size. By analyzing the chemical composition of the seed oil, we found that the content of unsaturated fatty acids was approximately 90%. Furthermore, the anti-oxidant activity of seed oil was assessed by a 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging assay and a β-carotene bleaching test. Yellow horn seed oil possessed notable concentration-dependent anti-oxidant activity with IC 50 values of 0.151 and 0.195 g/mL, respectively.